1123 DIAGNOSTIC ACCURACY OF SMART GADGETS/WEREABLE DEVICES IN ATRIAL FIBRILLATION DETECTION: A METANALYSIS. (15th December 2022) - Vetta, Giampaolo; Parlavecchio, Antonio; Gianni, Carola; Cipolletta, Laura; Polselli, Marco; Vuono, Francesco De; Pannone, Luigi; Mohanty, Sanghamitra; Cauti, Fillippo Maria; Caminiti, Rodolfo; Miraglia, Vincenzo; Monaco, Cinzia; et al.
Abstract: Introduction: Atrial fibrillation (AF) is the most common sustained arrhythmia and an important risk factor for stroke and heart. Recent technology advances have allowed for heart rhythm monitoring using smart gadgets/wearable devices which can be used for early AF diagnosis. Hypothesis: We performed a systemic review and meta-analysis to assess the accuracy of AF diagnosis by smart gadgets/wearable devices. Methods: We systematically searched Medline, Embase and Cochrane electronic databases up to April 15 th, 2022 for observational studies of the diagnostic accuracy of smartphone application, wrist-worn wearables and external devices in detecting AF. We calculated the area under the curve (AUC) of the summary receiver operating characteristic curves (SROC) and pooled sensitivities and specificities. Results: A total of 79 studies were included enrolling 36903 patients, 66.3% male with average age of 68.3±8 years. In the overall analysis of all devices, the AUC was 0.99 (95% CI: 0.98-1.00), the sensitivity 95%(95% CI: 94–96%), the specificity 96%(95% CI: 96–97%). Wrist-worn wearables had AUC of 0.99 (95% CI: 0.98-1.00), the sensitivity 95%(9% CI: 92–97%), the specificity 97%(95% CI: 96–98%)(Figure 1A). Smartphone applications had AUC of 0.98 (95% CI: 0.96-0.99), the sensitivity 96%(9% CI: 94–97%), the specificity 96%(95% CI: 93–98%)(Figure 1B). External devices had AUC of 0.99 (95% CI: 0.98-1.00), the sensitivity 95%(9% CI: 93–97%), the specificity 96%(95% CI: 95–97%)(Figure 1C). Single-lead ECG had AUC of 0.99 (95% CI: 0.98- 1.00), the sensitivity 95%(9% CI: 92–96%), the specificity 96%(95% CI: 95–97%). PPG had AUC of 0.99 (95% CI: 0.98-1.00), the sensitivity 96%(9% CI: 95–97%), the specificity 97%(95% CI: 95–98%). Conclusions: Smartphone application, wrist-worn devices and external devices with PPG and single-lead ECG have excellent diagnostic accuracy in atrial fibrillation diagnosis. Figure 1. Summary Receiver Operating Characteristic curves and Areas Under The Curve of Wrist-worn wearables (A), Smartphone applications (B) and External devices (C).